Assessment of the effects of best environmental practices on reducing pesticide contamination in surface water, using multi-criteria modelling combined with a GIS. (1st January 2013) - Macary, Francis; Almeida-Dias, Juscelino; Uny, Daniel; Probst, Anne
For half a century, the significant development of intensive farming has led to a massive use of products such as pesticides. The excessive use of these substances has contaminated surface water and groundwater. Some drinking water extraction points have also had to be abandoned. Around 30 years ago, in the southwest of France, a group of farmers decided to improve their farming methods, as well as developing new best environmental practices, such as grass strips along streams and riparian forests. By combining ELECTRE TRI-C, a sorting multi-criteria model, with a GIS, we were able to assign each farming parcel to one of the five levels of risk associated with surface water pesticide contamination. We also assessed the effectiveness of best environmental practices, and found that their use led to a reduction in the risk of pesticide transfer. This methodology re-enforces decision support tools for both water resource managers and agricultural and environmental stakeholders.